Law of universal gravitation with finite velocity of gravity and mathematical model of motion of a finite number of material points - Slyusarchuk, Vasyl (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2020)
The law of universal gravitation is intro- duced taking into account the finiteness of the gravi- tational velocity. Based on this law, a mathematical model of the motion of a finite number of material points is constructed, a separate case of which is the classical model of the motion of points, which is de- scribed by a system of ordinary differential equations. The constructed model is a system of nonlinear dif- ferential equations with deviating argument and func- tional equations. It more accurately describes the dy- namics of a finite number of material points than the corresponding classical model. A mathematical model of the motion of two material points is also considered.